(untitled) (Conversatoria Linguistica, 2019)
The article is devoted to linguistic means of religions practice so important for spiritual growth of man and his relationship with God. Semantic and functional analyses were conducted on the basis of dialectical data collected from the Central Poland. In the rich and diversified lexical-phraseological field attention was paid on: the Christian terms common with the Polish Nationwide language, the names typical for everyday language and dialects, the considerable differentiation of linguistic means, stylistic and expressive marking of some derivatives and linguistic processes, which are typical for discussed lexicon.